Les frontières de la violence au Kenya - Claire Médard (EchoGéo)
During the recent post electoral crisis in Kenya, the turn of the protest took many by surprise. We were reminded that the making of ethnicity is on ongoing process in which violence plays a part. New boundaries have appeared, re-enacting old divisions and creating new rifts. Once the mark of administration, internal boundaries now threaten the existence of the State.